2005
DOI: 10.1213/01.ane.0000167383.44984.e5
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Room Delirium Predicts Postoperative Delirium After Hip-Fracture Repair

Abstract: In patients undergoing hip-fracture repair, recovery room delirium is a strong predictor of postoperative delirium when using a standardized protocol for general anesthesia and postoperative pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 18 publications
6
98
0
6
Order By: Relevance
“…4 The mechanism whereby intraoperative sedation level affects the occurrence of postoperative delirium in elderly patients has not been elucidated. Hypotheses range from a cerebrovascular origin due to decreased perfusion associated with greater anesthetic depth in more deeply sedated patients, to toxicity of the larger doses of propofol administered to the deep sedation group, to a fundamental alteration in brain activity induced by deeper sedation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The mechanism whereby intraoperative sedation level affects the occurrence of postoperative delirium in elderly patients has not been elucidated. Hypotheses range from a cerebrovascular origin due to decreased perfusion associated with greater anesthetic depth in more deeply sedated patients, to toxicity of the larger doses of propofol administered to the deep sedation group, to a fundamental alteration in brain activity induced by deeper sedation.…”
Section: Discussionmentioning
confidence: 99%
“…The study was powered by assuming a prevalence of postoperative delirium of 0.36 in the deep sedation group, similar to that observed after hip fracture repair in elderly patients under general anesthesia, 4 and a prevalence of 0.12 in the light sedation group, similar to that seen after knee replacement in elderly patients under epidural anesthesia with sedation. 40 On the basis of these assumptions, each group would require 49 patients to achieve a power of 0.80 at a significance level of .05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium is an acute and fluctuating alteration of mental state of reduced awareness and disturbance of attention. POD (Post Operative Delirium) often starts in the recovery room and occurs up to 5 days after surgery [3][4][5]. One investigation [4] found that many patients with POD on the peripheral ward already had POD in the recovery room.…”
mentioning
confidence: 99%
“…POD (Post Operative Delirium) often starts in the recovery room and occurs up to 5 days after surgery [3][4][5]. One investigation [4] found that many patients with POD on the peripheral ward already had POD in the recovery room.More than 230 million surgical procedures are performed each year worldwide, of which more than 80 million are in Europe [6][7][8]. In Europe, the in-hospital mortality rate up to a maximum of 60 days is 3% after elective surgery and nearly 10% after emergency surgery [7].…”
mentioning
confidence: 99%